2015
DOI: 10.5267/j.ccl.2015.7.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel 1,5-benzothiazepin-4(5H)-ones as potent antiangiogenic and antioxidant agents

Abstract: Novel 1,5-benzothiazepin-4-(5H)-one derivatives (8a-8g) have been synthesized by intramolecular cyclization of 6 using propyl phosphonic anhydride (T3P) as a cyclodehydrating agent. The anti-angiogenic and anti-oxidant properties of the new derivatives were then evaluated. Compounds 8b, 8d, 8e, 8f and 8g exhibited very good inhibition of capillary proliferation, thus proving their anti-angiogenic properties. In addition, the in vitro antioxidant activities of these compounds were evaluated using diphenyl picry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…However, there are only a few studies reported that discuss the synthesis of the title compound in the literature. 9,10 Herein, we report an efficient route to prepare the title compound. Compared with the original research patent, we have shortened the reaction time of the last step (from 17 h to 30 min) and reduced the reaction temperature (from 190 °C to 130 °C).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few studies reported that discuss the synthesis of the title compound in the literature. 9,10 Herein, we report an efficient route to prepare the title compound. Compared with the original research patent, we have shortened the reaction time of the last step (from 17 h to 30 min) and reduced the reaction temperature (from 190 °C to 130 °C).…”
Section: Introductionmentioning
confidence: 99%